Global research trends in biomarkers, therapeutic targets, and drugs for amyotrophic lateral sclerosis: a bibliometric and visualization analysis - Guo, Na; Huang, Weicheng; Huang, Jianliang; Liu, Ying; Zhu, Kai; Gao, Wei (Frontiers in Pharmacology, 2025)
BackgroundAmyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive degeneration of motor neurons, marked by complex pathological mechanisms and a lack of effective treatments. Despite substantial global research efforts, no comprehensive bibliometric analysis has systematically mapped the evolution of ALS biomarkers, therapeutic targets, and pharmacological advancements.MethodsThis study, based on 4,250 publications retrieved from the Web of Science Core Collection (2005–2025), employs bibliometric tools such as CiteSpace and VOSviewer to conduct the first multidimensional analysis of global trends in ALS biomarkers, therapeutic targets, and drug research.ResultsThe results revealed contributions from 20,168 authors across 92 countries, with annual publications growing at an average rate of 16.5%. The United States dominated research output, accounting for 34.07% (n=1,448, TLCS=7,100), while the United Kingdom achieved the highest research impact with an average of 68 citations per article. Leading institutions, including the University of Oxford and the University of Milan, consistently produced high-impact studies. Pioneering scholars such as Turner MR and Kiernan MC made significant contributions to advancing therapeutic targets and drug discovery. The interdisciplinary integration of molecular biology and genetics emerged as a core driver of progress in ALS research. Neurofilament light chain (NfL), antisense oligonucleotide (ASO) drugs, transcranial magnetic stimulation (TMS), oxygen free radicals (oxidative stress), and gene therapy have consistently remained central research focuses in the ALS therapeutic field. Looking ahead, stem cell therapy, blood-brain barrier (BBB) penetration technologies, and skeletal muscle targeting are poised to emerge as prominent research directions.ConclusionThe United States dominates ALS research productivity, whereas the United Kingdom demonstrates superior citation influence. Despite China’s substantial publication volume, its limited citation impact underscores the necessity for enhanced methodological rigor and strategic international collaboration. Current research priorities encompass NfL, TMS, and ASO therapies, with emerging innovations in stem cell therapy, BBB penetration technologies and skeletal muscle targeting showing therapeutic promise. Future directions should prioritize biomarker standardization, optimization of drug delivery systems, and Clinical Translation.